Efektifitas Kebijakan Peminjaman Buku di Digital Library Universitas Negeri Medan - Griyani Elisabeth Purba; Adelina Sitanggang; Depi Yohana Manurung; Tessa Lonika Simanullang (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to evaluate the effectiveness of the book lending policy at the Digital Library of the State University of Medan (UNIMED) and explore student responses to the policy. The method used is a qualitative descriptive approach, with data collection through interviews and observations in the Digital Library building. The results of the study show that most students understand and feel helped by the new policy that requires the use of digital applications for book borrowing, which is considered to improve accessibility and convenience. However, there are concerns about the security of personal data, as well as dissatisfaction regarding the withdrawal of physical library cards. Overall, while this policy is effective, there is still a need for improvement, especially in the aspects of data security and better socialization. The proposed recommendations include improving security systems, more intensive policy socialization, and the development of additional in-app features to improve the user experience.